Konsep Sustainable Bangunan Green School Building Bali Pengaruhnya pada Pelajar - Arina Sabila (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Green School Bali is a school located in the middle of a forest area surrounded by lush organic gardens, and crossed by the Ayung River. This school has received much praise from all over the world because its learning methods combine academic learning with environmentally friendly practices. In addition, there is something interesting about the building in this school, namely the Green School building is very much in harmony with nature using the concept of Green Architecture and Sustainable. It is known that buildings with the concept of Green Architecture and Sustainable are very different from the average school in Indonesia. One of them is applying bamboo material as the main structural material of the school and there are many more interesting things in the Green School building in Bali. This study uses a descriptive method from several sources of scientific work. This criticism aims to determine whether the application of the Green School building concept in education can affect the talents and artistic of students.